2006
DOI: 10.1111/j.1601-183x.2006.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex, multimodal behavioral profile of the Homer1 knockout mouse

Abstract: Proteins of the Homer1 immediate early gene family have been associated with synaptogenesis and synaptic plasticity suggesting broad behavioral consequences of loss of function. This study examined the behavior of male Homer1 knockout (KO) mice compared with wildtype (WT) and heterozygous mice using a battery of 10 behavioral tests probing sensory, motor, social, emotional and learning/memory functions. KO mice showed mild somatic growth retardation, poor motor coordination, enhanced sensory reactivity and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 74 publications
(173 reference statements)
15
57
0
Order By: Relevance
“…Absence of Homer-1a protein in knockout mice resulted in water maze performance deficits (Jaubert et al 2007), similar to those observed in the present study in the aged group. Furthermore, Homer-1a knockout mice have been shown to be critical for long-term fear memory formation (Inoue et al 2009).…”
Section: Discussionsupporting
confidence: 78%
“…Absence of Homer-1a protein in knockout mice resulted in water maze performance deficits (Jaubert et al 2007), similar to those observed in the present study in the aged group. Furthermore, Homer-1a knockout mice have been shown to be critical for long-term fear memory formation (Inoue et al 2009).…”
Section: Discussionsupporting
confidence: 78%
“…We further observed a strong hyperactive phenotype because of Homer1 deletion that has been previously reported in studies that employed this mouse model (Szumlinski et al, 2005;Jaubert et al, 2007). These hyperactive behaviors in general led to an apparent reversal of the CSDS-induced phenotype that was mostly visible in locomotive and social behavior.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast, the early immediate gene Homer1a is thought to act as dominant negative isoform disrupting mGluR5/Homer1b/c coupling and predominantly modulates ligand-independent mGluR5 signaling (Ango et al, 2001). Clinical studies provided first evidence that Homer1 is involved in the development of major depressive disorders (Rietschel et al, 2010), whereas preclinical studies describe its importance in anxiety-and depression-related behavior (Szumlinski et al, 2005;Lominac et al, 2005), memory formation , fear (Tronson et al, 2010), and reward-related behaviors (Jaubert et al, 2007;Szumlinski et al, 2004). Furthermore, the activityinduced splice variant Homer1a (Brakeman et al, 1997) has been shown to be crucially involved in behavioral alterations that are related to depression (Celikel et al, 2007;Mahan et al, 2012) and anxiety .…”
Section: Introductionmentioning
confidence: 99%
“…However, prenatally stressed animals exhibit profound cognitive, social and sensorimotor deficits [304,305] and increased sensitivity to the psychomotor-activating, motivational and glutamate-sensitizing effects of stimulant drugs as adults [294,295,306]. Interestingly, the behavioral and glutamate phenotype induced by prenatal stress bears striking resemblance to that produced by Homer1 deletion [34,172,173,307]. Thus, stressor-induced imbalances in IEG-and CC-Homer expression within corticolimbic structures may alter the development trajectory of corticolimbic circuits, thereby increasing the propensity to develop addictionrelated behaviors in later life [157,220].…”
Section: Stressor-induced Regulation Of Homers: Implications For Addimentioning
confidence: 99%
“…While analyses for polymorphisms in the Homer genes have not yet been assessed in a co-morbid population, single nucleotide polymorphisms in Homer1 have been associated with cocaine addiction [241], as well as in schizophrenia (IVS4 + 18A > G in intron 4) [326]. In addition to exhibiting increased sensitivity to the rewarding and psychomotoractivating effects of psychomotor stimulants, Homer1 KO mice exhibit a host of other behavioral abnormalities, including deficits in working memory, pre-pulse inhibition of acoustic startle, instrumental learning and habituation to a mild stressor, as well as increases in emotional reactivity to mild stressors and behavioral despair [34,172,173,307]. Moreover, Homer1 KO mice exhibit increased behavioral sensitivity to NMDA receptor antagonists [34,38,172] and both the deficit in pre-pulse inhibition and the increased sensitivity to phencyclidine can be reversed by pretreatment with either typical or atypical antipsychotic drugs [172;Richardson and Szumlinski,in preparation].…”
Section: Homers Addiction and Schizophrenia Co-morbiditymentioning
confidence: 99%